STUDI PERANCANGAN ANTENA MICROSTRIP MONOPOLE BENTUK PATCH SEGITIGA DENGAN TEKNIK DEFECTED GROUND STRUCTURE UNTUK APLIKASI ULTRA-WIDEBAND - M Darsono; Dwi Widiatmoko (Jurnal Teknologi Terapan, 2022)
Study on the design of a microstrip monopole antenna as a form of support and development of UWB (Ultra-Wideband) wireless communication devices. The basic concept of the proposed antenna design is minimalist with the characteristics of operating on broadband in accordance with those regulated by the FCC (Federal Communications Commission). The design of a planar type of microstrip antenna with triangular radiation using the DGS (Defected Ground Structure) technique for the design of a trapezoidal ground plane. As support in this research, Duroid RT 5880 substrate material and CST software were used for the simulation method. The results of the simulation method obtained are twofold: The shape of the antenna design configuration is minimalist and compact and the antenna performance parameters. For antenna performance parameters obtained through simulation methods, such as the fractional bandwidth of return loss below 10 dB is 3.8:1 (VSWR < 2), and the maximum power radiation transmittance is 2.59dBi, forming an omnidirectional radiation pattern with vertical polarization. The characteristics of the operating performance of the antenna on the UWB spectrum are able to cover the frequency area in the C-Band and X-band and in the application, the antenna design supports wireless LAN communication and satellite communication systems.